Correlative Factors of PD-1/PD-L1 Inhibitors-based Immunotherapy Responses in Non-small Cell Lung Cancer - Wang, Caiwei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The use of immunotherapy as a treatment modality in the field of cancer has garnered significant attention since its discovery. Among these, studies have demonstrated the substantial benefits of using programmed death 1 (PD1)/programmed death ligand 1 (PD-L1) inhibitors in the treatment of non-small cell lung cancer (NSCLC). However, as research continues, there are differing advantages and disadvantages to this treatment for NSCLC. Adverse effects related to the immune system and high costs are also faced by patients undergoing this therapy. As a result, the creation of biomarkers is crucial for the immunotherapy of cancer. Numerous studies have examined immunotherapy’s side effects in non-small cell lung cancer. Therefore, on the basis of previous studies, this article reviews the factors related to the involvement of PD-1/PD-L1 inhibitors in the immunotherapy response of NSCLC, in order to find candidate drugs and more effective biological treatments for PD-1/PD-L1 inhibitors. Markers provide direction and theoretical basis.